On the development of the real estate market in the developing cities of central Siberia ("Journal "U". Economy. Management. Finance.", 2023)
Real estate analysis in the developing cities of Central Siberia is a hot topic in the modern world of real estate. This paper discusses the main directions of development of the real estate market in the cities of the region: Omsk, Krasnoyarsk, Novosibirsk, Irkutsk, etc. The possibility of improving housing conditions in developing cities of Central Siberia, analyzing the situation on the housing market, developing a model for improving housing conditions.
Keywords: housing; housing conditions; statistical indicators; quality of life; real estate; real estate market; housing prices; construction volumes; government programs